TRANSLATING IN ANCIENT ROME: FRAGMENTS OF A RENOVATED LITERATURE - Vieira, Brunno V. G. [UNESP] (Univ Estadual Paulista, Fundacao Editora Unesp, 2022)
Among his ideas on translation found in De optimo genere oratorum, Cicero points out that it is necessary to translate Aeschines and Demosthenes as orator and not as interpres. This objection may reflect an indication of another trend of translation, which proposed a literal translation, based more on the materiality of the source language than on the transposition of its style (elocutio). If Cicero in theory and in practice offers examples of what it means to translate as orator, he leaves open the practices of interpres. In this paper, I propose to outline some scattered fragments of translations from the end of the Republic and the beginning of the Empire that testify this perspective, bringing a reflection on the heterogeneity of translation practices in Ancient Rome.
Keywords: De optimo genere oratorum; elocutio; interpres; translation in Antiquity; Cicero